Bach ho field geological features identification using well logging data; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 334, № 7 - Nguyen Xuan Kha; Pham Xuan Son; Hoang Van Quy; Nguyen Tuan; Truong Quoc Thanh; Mai Huu Xuan; Tran Van Xuan (2023, 2023)
Заглавие с титульного листа